Inverted Nutcracker Syndrome: A Case of Persistent Hematuria and Pain in the Presence of a Left-Sided Inferior Vena Cava - Obi Ekwenna; Michael A. Gorin; Miguel Castellan; Victor Casillas; Gaetano Ciancio (The Scientific World Journal)
Nutcracker syndrome is described as the symptomatic compression of left renal vein between the aorta and the superior mesenteric artery, resulting in outflow congestion of the left kidney. We present the case of a 51-year-old male with a left-sided inferior vena cava, resulting in compression of the right renal vein by the superior mesenteric artery. Secondary to this anatomic anomaly, the patient experienced a many-year history of flank pain and intermittent gross hematuria. We have termed this unusual anatomic finding and its associated symptoms as the “inverted nutcracker syndrome”, and describe its successful management with nephrectomy and autotransplantation.